P-selectin glycoprotein ligand-1 mediates rolling of human neutrophils on P-selectin (The Rockefeller University Press, 1995)
Neutrophils roll on P-selectin expressed by activated platelets or endothelial cells under the shear stresses in the microcirculation. P- selectin glycoprotein ligand-1 (PSGL-1) is a high affinity ligand for P- selectin on myeloid cells. However, it has not been demonstrated that PSGL-1 contributes to the rolling of neutrophils on P-selectin. We developed two IgG mAbs, PL1 and PL2, that appear to recognize protein- dependent epitopes on human PSGL-1. The mAbs bound to PSGL-1 on all leukocytes as well as on heterologous cells transfected with PSGL-1 cDNA. PL1, but not PL2, blocked binding of 125-I-PSGL-1 to immobilized P-selectin, binding of fluid-phase P-selectin to myeloid and lymphoid leukocytes, adhesion of neutrophils to immobilized P-selectin under static conditions, and rolling of neutrophils on P-selectin-expressing CHO cells under a range of shear stresses. PSGL-1 was localized to microvilli on neutrophils, a topography that may facilitate its adhesive function. These data indicate that (a) PSGL-1 accounts for the high affinity binding sites for P-selectin on leukocytes, and (b) PSGL- 1 must interact with P-selectin in order for neutrophils to roll on P- selectin at physiological shear stresses.